SARANA BERPIKIR ILMIAH: BAHASA, DEFINISI, MATEMATIKA, DAN STATISTIKA - Erni Haryanti; Muttaqin, Via Putrimawati; Nurdiansyah, Achmad; Saadah, Susi (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
Thinking is the process of reason in getting ideas from knowledge or science. Thinking is a means that can help humans obtain innovation that is in line with the needs in their lives. Therefore, scientific thinking is a proper thing for a human being. Scientific thinking is carried out through how thoughts are created, including using language, definitions, mathematics, and statistics. So the aim of this article is: 1) Knowing the means of scientific thinking, 2) language as a means of scientific thinking, 3) definitions as a means of scientific thinking, 4) mathematics as a means of scientific thinking, 5) statistics as a means of scientific thinking. The method used in this study uses a descriptive qualitative approach with library methods. The results of this research are that humans can develop and create new things, but because of the limitations they have, humans need tools to pursue new things that they want to know, these tools are called scientific thinking tools. Among them are language, a communicative function and a cultural tool that unites people, definitions are used as a practical aspect for constructing theories, mathematics is used as a deductive thinking tool, and statistics helps make generalizations and conclude the characteristics of a phenomenon with more certainty, as well as providing opportunities or probabilities that for certain premises, the conclusions drawn may be true or false.